The Legal Status of Wills in Islamic Law: A Juridical Analysis - Hasibuan, Putra Halomoan (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
The article discusses the scope of wills, the legal basis for wills, types of wills, the pillars of a will, the requirements for the validity of a will, wills to heirs, limitations on wills, the number of wills, the cancellation and invalidation of a will, the revocation of a will, and the procedures involved. It then addresses the Islamic legal perspective on the execution of a will. This research uses a qualitative approach with literature study as the main data collection method. The conclusion is that the legal status of a will differs from one person to another depending on the circumstances, namely it is obligatory for someone if it is feared that the property left behind will be squandered. It is considered sunnah if the will is for charitable purposes, such as a will to relatives, the construction of mosques, schools, or other public interests. It is haram if the will can harm the heirs. This study provides both theoretical and practical contributions to the field of Islamic law, particularly in the area of fiqh al-wasiyyah (Islamic jurisprudence on wills). Using a qualitative approach and literature study as the primary data collection method, the article offers a comprehensive analysis of various aspects of testamentary wills, including their legal basis, types, pillars and validity requirements, limitations, revocation procedures, and execution mechanisms. Keywords: Islamic Law, Legal Status, Wills